2017
DOI: 10.1159/000479914
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of Cxcl10 Inhibits Mesangial Cell Proliferation in Murine Habu Nephritis Via ERK Signaling

Abstract: Background/Aims: IFN-γ-inducible protein 10 (IP-10, CXCL10) has been widely demonstrated to be involved in chemotaxis, cell growth regulation and angiogenesis inhibition. It has been reported that CXCL10 expression is significantly increased in patients with MesPGN (Mesangial proliferative glomerulonephritis). However, the underlying mechanism of CXCL10 in MesPGN reminds unclear. Methods: Wildtype (Cxcl10+/+) mice and Cxcl10-deficient (Cxcl10-/-) mice were used to generate a murine model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 41 publications
2
12
0
Order By: Relevance
“…To further investigate the proliferation effect of CXCL10 in MesPGN, our previous study used Cxcl10-deficient mice (Cxcl10 -/mice) to generate a Habu nephritis model, a classical experimental model that develops glomerular lesions similar to those of human MesPGN, and found that Cxcl10 -/mice exhibited mitigated proliferation with less extracellular matrix accumulation and fewer cells in the glomeruli compared with wild-type mice in the mesangial proliferation period, which peaked on day 7 after HSV injection. In addition, we hypothesized that CXCL10 modulates cell cycle regulatory proteins to promote mesangial proliferation via the ERK signaling pathway, as confirmed in vitro using primary mouse mesangial cells [55]. Our data, together with those reported previously by Romagnani et al, were consistent with a cell type-specific proliferative effect of CXCL10 and suggested the potential therapeutic target of CXCL10 on cell proliferation.…”
Section: Mesangial Proliferative Glomerulonephritis (Mespgn)supporting
confidence: 90%
“…To further investigate the proliferation effect of CXCL10 in MesPGN, our previous study used Cxcl10-deficient mice (Cxcl10 -/mice) to generate a Habu nephritis model, a classical experimental model that develops glomerular lesions similar to those of human MesPGN, and found that Cxcl10 -/mice exhibited mitigated proliferation with less extracellular matrix accumulation and fewer cells in the glomeruli compared with wild-type mice in the mesangial proliferation period, which peaked on day 7 after HSV injection. In addition, we hypothesized that CXCL10 modulates cell cycle regulatory proteins to promote mesangial proliferation via the ERK signaling pathway, as confirmed in vitro using primary mouse mesangial cells [55]. Our data, together with those reported previously by Romagnani et al, were consistent with a cell type-specific proliferative effect of CXCL10 and suggested the potential therapeutic target of CXCL10 on cell proliferation.…”
Section: Mesangial Proliferative Glomerulonephritis (Mespgn)supporting
confidence: 90%
“…43 Recently, a series of studies showed that CXCL10 also could play roles in regulating cell proliferation, apoptosis, differentiation, and angiogenesis. [24][25][26][27] Our finding that expression of CXCL10 was accompanied by an increase of IFN-γ at the late stage after injury, while the inflammatory cells were recruited from circulation mainly at the early stage after injury, hints a novel role of CXCL10 in skeletal muscle repair. We found that MuSCs also expressed the receptor of CXCL10 and CXCR3.…”
Section: Discussionmentioning
confidence: 84%
“…Despite its chemotactic nature, CXCL10 is also reported to be a cytokine associated with cell proliferation, apoptosis, differentiation, and angiogenesis. [24][25][26][27] The receptor of CXCL10 is CXCR3, a G protein-coupled receptor expressed mainly in immune cells and other somatic cells. In uninjured young muscle, CXCR3 was expressed mostly in CD45 À CD31 À α7integrin + MuSCs (75.7%) as assessed by flow cytometry.…”
Section: Cxcl10 Promotes the Proliferation Of Muscle Satellite Cells mentioning
confidence: 99%
“…The activated and proliferative mesangial cells in the glomerulus could produce kinds of vasoactive substances and cytokines including interleukin-1 (IL-1), interferon (IFN) and chemotactic factor (CXC), thereby promoting ongoing mesangial cell proliferation (Gao et al, 2017). In fact, inflammation plays a key role in the development of MPGN, including anti-Thy1 nephritis and IgA nephropathy animal models (Hua et al, 2013; Aizawa et al, 2014).…”
Section: Discussionmentioning
confidence: 99%